Clustering Tingkat Kekerasan pada Anak Dan Perempuan Berdasarkan Jenis Kekerasan Yang Dialami di Sumatera Utara 2023 - Nasution, Marnis (Journal of Student Development Information System (JoSDIS), 2025)
This study aims to analyze the level of violence against children and women in North Sumatra in 2023 using the K-Means clustering method. The data was obtained from the Department of Women's and Children's Protection, covering various forms of violence occurring in different regions. The analysis was conducted using RapidMiner software, with the optimal number of clusters determined to be five (K=5). The clustering results reveal patterns in the distribution of violence cases based on specific characteristics, which can serve as a foundation for the government and policymakers to formulate more effective strategies for preventing and addressing violence against children and women.